PbGA20ox2 Regulates Fruit Set and Induces Parthenocarpy by Enhancing GA4 Content - Wang, Huibin; Wu, Ting; Liu, Jianlong; Cong, Liu; Zhu, Yanfei; Zhai, Rui; Yang, Chengquan; Wang, Zhigang; Ma, Fengwang; Xu, Lingfei (Frontiers in Plant Science, 2020)
Fruit set and development occur following successful fertilization. Parthenocarpy, a valuable trait in some self-incompatible species, produces seedless fruit without fertilization. Gibberellin (GA) is a crucial hormone in fruit-set regulation and development. While investigating the development of parthenocarpy in pear (Pyrus bretschneideri Rehd.), we determined that GA 20-oxidases (GA20ox) may play key roles in seedless pear fruit development. Sequence analysis revealed three PbGA20ox genes: PbGA20ox1, PbGA20ox2, and PbGA20ox3. We analyzed the expression patterns of candidate genes and found that PbGA20ox2 levels significantly changed in pollinated fruits. Tissue-specific expression assays revealed that PbGA20ox2 is highly expressed in young fruit and leaves. Subcellular localization assays showed it was located in the cytoplasm, nucleus and plasma membrane. Overexpressed PbGA20ox2 tomato plants were taller and had longer hypocotyls and internodes, and the emasculated flowers produced parthenocarpic fruit. In pear, the transient overexpression of PbGA20ox2 promoted fruit development and delayed the drop of non-pollinated fruit. Furthermore, the fruit of PbGA20ox2-overexpressing tomato and transient PbGA20ox2-overexpressing pear had increased GA4 (but not GA3 and GA1) contents. This result provided evidence that PbGA20ox2 was necessary for GA4-dependent pear fruit development. Our study revealed that PbGA20ox2 altered the GA biosynthetic pathway and enhanced GA4 synthesis, thereby promoting fruit set and parthenocarpic fruit development.